Food Symbolism in the World of Vision of Piers Plowman - Valentina S. Sergeeva (Studia Litterarum)
W. Langland’s allegorical poem Vision of Piers Plowman is one of the key works of the medieval religious literature. Scenes of eating or drinking are among its most important episodes. The sacral meaning of food in the poem originates in the context of medieval theology appearing around certain evangelic images (“I am the bread of life,” etc.) Each time when the characters eat or drink the realization of Christian dogmas is having place, or, on the contrary, they are refused, because the abundance of “daily bread” leads to spiritual deafness. Gluttony goes hand in hand with hypocrisy, and in the world of the poem it appears not only as over-eating but also as rejecting any real Christian practice. A glutton wastes goods he could give out to the needy, as well as the treasures of his soul; and if he is of the learned, he deprives the “little ones” of their spiritual repast, too. W. Langland includes everyday events and doings into the supertemporal Bible narrative, thus actualizing them for all his Christian readers. As the result of such text organization, food-related episodes appear to be linking spots for the main themes of the poem (Christian life, charity, love, knowledge).